Insulin-Like Growth Factor-1 and Neuroinflammation - Labandeira-Garcia, Jose L.; Costa-Besada, Maria A.; Labandeira, Carmen M.; Villar-Cheda, Begoña; Rodríguez-Perez, Ana I. (Frontiers in Aging Neuroscience, 2017)
IGF-1 effects on aging and neurodegeneration is still controversial. However, it is widely admitted that IGF-1 is involved in the neuroinflammatory response. In peripheral tissues, several studies showed that IGF-1 inhibited the expression of inflammatory markers, although other studies concluded that IGF-1 has proinflammatory functions. Furthermore, proinflammatory cytokines such as TNF-α impaired IGF-1 signaling. In the brain, there are controversial results on effects of IGF-1 in neuroinflammation. In addition to direct protective effects on neurons, several studies revealed anti-inflammatory effects of IGF-1 acting on astrocytes and microglia, and that IGF-1 may also inhibit blood brain barrier permeability. Altogether suggests that the aging-related decrease in IGF-1 levels may contribute to the aging-related pro-inflammatory state. IGF-1 inhibits the astrocytic response to inflammatory stimuli, and modulates microglial phenotype (IGF-1 promotes the microglial M2 and inhibits of M1 phenotype). Furthermore, IGF-1 is mitogenic for microglia. IGF-1 and estrogen interact to modulate the neuroinflammatory response and microglial and astrocytic phenotypes. Brain renin-angiotensin and IGF-1 systems also interact to modulate neuroinflammation. Induction of microglial IGF-1 by angiotensin, and possibly by other pro-inflammatory inducers, plays a major role in the repression of the M1 microglial neurotoxic phenotype and the enhancement of the transition to an M2 microglial repair/regenerative phenotype. This mechanism is impaired in aged brains. Aging-related decrease in IGF-1 may contribute to the loss of capacity of microglia to undergo M2 activation. Fine tuning of IGF-1 levels may be critical for regulating the neuroinflammatory response, and IGF-1 may be involved in inflammation in a context-dependent mode.